REWRITING THE HISTORY OF HELL THROUGH THE 21ST-CENTURY SCENE IN DAN BROWN’S INFERNO - Maram OUERTATANI (ACROSS)
The twenty-first century is an era of radical, unexpected and fast changes in the political, social and cultural scene. Reality has become a slave to the socio-political interventions and instability leading to numerous questions rather than answers. The choice of Inferno is based on this observation of the 21st century as the rapid pace of changing events has stimulated a growing need for truth, reality and explanations. Brown’s cryptic plot and his claim of Fact [i] create the very focus of this paper which is the question of historicity in this text.  Put into the 21st century’s historical context, Brown revisits Dantean Inferno[ii] of The Divine Comedy[iii]  through the thematic focus on the overpopulation as a recent concern of the century, the metaphorical representation of characters, and their linguistic. As such, this paper will study the historicity of Brown’s Inferno[iv], highlight its parodic dimension, and unveil the hellish nature of the twenty-first century through the re-incarnation of the ancient fears into the present times and the deconstruction of the biblical image of hell.